Quasiparticle theory of defects in solids - PuÅ¡karov, D. I (World scientific, 1991)
6 chapters: Energy spectrum of Defectons in Quantum Crystals; defecton statistics and Thermodynamics; Kinetics of a Defecton Gas; Structure of a Quantum Crystal with Delocalized Defects;...